Clinical efficacy of intestinal stent placement combined with laparoscopic surgery in the treatment of obstructive left-sided colon cancer - Yang Zhigang; Che Minghua; Huang Hai; He Chengxiang (结直肠肛门外科)
[Objectives] To investigate the clinical efficacy of intestinal stent placement combined with laparoscopic surgery in the treatment of obstructive left-sided colon cancer. [Methods] Twenty-eight patients with left-sided colon cancer complicated with intestinal obstruction, who were admitted to the Department of General Surgery at Liqun Hospital in Putuo District, Shanghai from January 2016 to June 2022, were selected as the study subjects. Intestinal stent placement combined with laparoscopic surgery was performed in all the patients. The intestinal stent placement and relevant clinical parameters, as well as laparoscopic surgery-related indicators, were observed and recorded. [Results] All patients successfully underwent intestinal stent placement without displacement, detachment, or intestinal perforation. All patients underwent laparoscopic surgery two weeks later. The white blood cell count, hemoglobin level, albumin level, and blood potassium concentration of the patients before laparoscopic surgery were superior to those at admission (P < 0.05). No patients experienced intra-abdominal bleeding after laparoscopic surgery. Two patients had incision infection, while three required prophylactic terminal ileostomy. After three months, ileostomy closure was performed, with one patient experiencing anastomotic leakage. All affected patients recovered after conservative treatment, with no perioperative deaths recorded. [Conclusion] Intestinal stent placement combined with laparoscopic surgery offers a safe and reliable treatment approach for obstructive left-sided colon cancer. Preoperative intestinal stent placement effectively relieves intestinal obstruction symptoms, and provides a good opportunity for further laparoscopic surgery.